EPC Minutes 2005-03-24 - Academic Senate:::::::::
Educational Policies Committee. Provost Report. Statewide Senator Report. Vice Chair Report. Vice President of Administration and Finance Report. Chief Student Affairs Officer Report. EPC Report. Revision to the Psychology Major approved as consent item for Senate. FSAC Report. APC Report. SAC Report. Associated Students Report. Senate Agenda approved.